Cystic Kidney Diseases in Sudanese Children: Pattern, Clinical Presentation, and Outcome - Maali Alwathig Alameen; Ebtihal Eltyeb; Rashid Ellidir (Sudan Journal of Medical Sciences)
Background: Cystic kidney disease (CKD) can directly lead to chronic kidney disease in children. This study aims to determine the types, clinical presentation, and outcome of CKD in Sudanese children. Methods: This retrospective records-based study from January 2005 to December 2017 was conducted at Soba University Hospital, including patients with renal diseases coming from different parts of Sudan. Results: A total of 105 cases of CKD were identified out of 3050 medical records reviewed in this study, resulting in a prevalence of 3.4% among all pediatric admissions to the renal unit. Male represents 57.1%, and the mean age at presentation was 36.5 ± 4.5 months. The most frequent clinical presentation was a palpable abdominal mass followed by urinary tract infection and incidental presentation. About 15.2% presented with chronic renal failure, and neonatal presentations were reported in 6.6%. The most prevalent type was polycystic kidney disease (PCKD; 40.9%), followed by multicystic dysplastic kidney (MCDK; 36.2%). Autosomal dominant polycystic kidney disease (ADPCKD) and MCDK were present mainly in age groups <1 year old, compared to the cyst of the medulla related to age groups 5–9 and 10–14 years. The clinical outcome showed the absence of symptoms and normal renal function in 59% of the patients during follow-up notes. In comparison, 29.5% developed chronic kidney disease, of whom 11.4% were stage-five and required dialysis, while 8.6% required kidney transplantation, and death was reported in 11.4%. There was a significant statistical association between the type of disease and consanguinity (P = 0.018) and the age of presentation (P = 0.012). Conclusion: Five types of CKD were reported, with the predominance of polycystic kidney disease. Males and <1 year olds were more affected among children. Early detection and renal replacement therapy can improve the outcome in such cases.